Análise bibliométrica da produção científica sobre direitos das pessoas com deficiência - Bravo, Aline Droppé (2013)
The relationship between law and persons with disabilities existed since ancient times and is changing, albeit slowly, in search of human dignity. In the context of construction and warranty rights, scientific study was present, contributing new theories and mapping the social events. Thus, this study focuses on the rights of persons with disabilities in the Consolidated represented by scientific theses and dissertations in the Graduate Programs in the coun period between 1991 and 2009 and aims to: select the theses and dissertations in the period between 1991 and 2009 are available at the Bank of CAPES thesis and whose object of study people with disabilities and the law; analyze this scientific production, through bibliometric approach, methodology resource that allows, among other things, understand the configuration of certain knowledge areas from the analysis of the scientific production; produce bibliometric indicators of scientific output selected using the following parameters: authorship, institutional affiliation and professional profile of authors; encouragement received; regional and temporal distribution of the work; themes focused, among other , analyzing the content of selected theses and dissertations, by selecting a sample of at least one work linked to each knowledge area identified. As a theoretical framework we used the current law regarding the rights of persons with disabilities, as well as work on the analysis of scientific production and rights of people with disabilities. Regarding the methodology, the research is characterized as documentary, descriptive and analytical, based on bibliometric approach. The methodological procedures involved the following stages: a) literature review, b) survey and analysis of theses and dissertations involving thematic c) systematization and analysis of results. It was observed by the data obtained, among other things, that most research was developed between the years 2007 and 2009, and most often in programs related to the area of law and it was found that few institutions are responsible for developing most studies.